ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA MENURUT POLYA DITINJAU DARI GAYA KOGNITIF - Berek, Maria Delian Frilian; Sesanti , Nyamik Rahayu; Wahyuningtyas, Dyah Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Elementary school students have difficulty in solving problems, especially when solving story-shaped math problems. This study aims to describe students' math problem solving ability based on Polya's steps by considering cognitive style. This study used a descriptive qualitative approach and was conducted in class V in one of the elementary schools in Malang. The Group Embedded Figures Test (GEFT) instrument was used to identify students' cognitive styles, while data were collected through problem solving tests, interviews and documentation. The results showed that students with field independent cognitive style (FI) were able to complete the four steps of Polya systematically and independently, and able to recognize important information and develop appropriate solution strategies. In contrast, students with field dependent (FD) style had difficulty in understanding the problem and planning the solution, and require more direction. It can be concluded that cognitive style can have an impact on the success of students in solving story problems based on Polya's steps.